Earthquake weather - Powers, Tim, 1952- (Fault lines series, 2019)
The magical King of the West has been killed in California, and his assassin is one of the multiple personalities in the head of Janis Cordelia Plumtree--but which one? One of them is a streetwise pickpocket. Another is dead, and can only speak in quotes from Shakespeare. And another seems to be the unquiet ghost of her father. And there are many others. Sid Cochran is a one-time winemaker who blames his wife's suicide on the wine-god Dionysus, and believes that Dionysus is now pursuing him. Cochran and Plumtree escape together from a mental hospital in Los Angeles, and--pursued by ghosts, gangsters, and a crazy psychiatrist--set out for San Francisco and the wine country to try to restore the dead King of the West to life. But the god Dionysus himself is a player in this perilous game--and not on their side.